Fungal diversity notes 1818–1918: taxonomic and phylogenetic contributions on genera and species of fungi - Manawasinghe, Ishara S.; Hyde, Kevin D.; Wanasinghe, Dhanushka N.; Karunarathna, Samantha C.; Maharachchikumbura, Sajeewa S. N.; Samarakoon, Milan C.; Voglmayr, Hermann; Pang, Ka-Lai; Chiang, Michael Wai-Lun; Jones, E. B. Gareth; Saxena, Ramesh K.; Kumar, Arun; et al. (My University, 2024)
This article is the 17th in the Fungal Diversity Notes series which allows the researchers to publish fungal collections with updated reports of fungus-host and fungus-geography. Herein we report 97 taxa with four new genera distributed in three phyla (Ascomycota, Glomeromycota and Mucoromycota), 11 classes, 38 orders and 62 families collected from various regions worldwide. This collection is further classified into taxa from 69 genera with four novel genera namely Jinshana, Lithophyllospora, Parapolyplosphaeria and Stegonsporiicola. Furthermore, 71 new species, 21 new records, one new combination and four novel phylogenetic placements are provided. The new species comprise Acrocalymma estuarinum, Aggregatorygma isidiatum, Alleppeysporonites elsikii, Amphibambusa aquatica, Apiospora hongheensis, Arthrobotrys tachengensis, Calonectria potisiana, Collariella hongheensis, Colletotrichum squamosae, Corynespora chengduensis, Diaporthe beijingensis, Dicellaesporites plicatus, Dicellaesporites verrucatus, Dictyoarthrinium endophyticum, Distoseptispora chiangraiensis, Dothiora eucalypti, Epicoccum indicum, Exesisporites chandrae, Fitzroyomyces pseudopandanicola, Fomitiporia exigua, Fomitiporia rondonii, Fulvifomes subthailandicus, Gigaspora siqueirae, Gymnopus ailaoensis, Hyalorbilia yunnanensis, Hygrocybe minimiholatra, H. mitsinjoensis, H. parviholatra, H. solis, H. vintsy, Helicogermslita kunmingensis, Jinshana tangtangiae, Kirschsteiniothelia dujuanhuensis, Lamproderma subcristatum, Leucoagaricus madagascarensis, Leucocoprinus mantadiaensis, Lithophyllospora australis, Marasmius qujingensis, Melomastia aquilariae, Monoporisporites jansoniusii, M. pattersonii, Monoporisporites valdiyae, Mucispora maesotensis, Mucor soli, Muyocopron yunnanensis, Nigrospora tomentosae, Ocellularia psorirregularis, Ophiocordyceps duyunensis, Oxneriaria nigrodisca, Oxydothis aquatica, O. filiforme, Phacidiella xishuangbannaensis, Phlebiopsis subgriseofuscescens, Pleurothecium takense, Pleurotus tuber-regium, Pseudochaetosphaeronema puerensis, Pseudodactylaria guttulate, Racheliella chinensis, Rhexoacrodictys fangensis, Roussoella neoaquatica, Rubroboletus pruinosus, Sanghuangporus subzonatus, Scytalidium assmuthi, Shrungabeeja kudremukhensis, Spirographa skorinae, Stanjehughesia bambusicola, Stegonsporiicola aurantiaca, Umbelopsis hingganensis, Vararia tenuata, Verruconis pakchongensis, Wongia bandungensis, and Zygosporium cymodoceae. The new combination is Parapolyplosphaeria thailandica (≡ Polyplosphaeria thailandica). The 21 new hosts, geographical and habitat records comprise Acrocalymma fici, Apiculospora spartii, Aspergillus subramanianii, Camposporium ramosum, Clonostachys rogersoniana, Colletotrichum brevisporum, C. plurivorum, Collybiopsis gibbosa, Dictyosporium tratense, Distoseptispora adscendens, Exosporium livistonae, Ganoderma gibbosum, Graphis mikuraensis, Gymnosporangium paraphysatum, Lasiodiplodia thailandica, Moesziomyces bullatus, Penicillium cremeogriseum, P. echinulonalgiovense, P. javanicum, P. lanosocoeruleum, P. polonicum, and Pleurotus tuber-regium. Graphis chlorotica, G. panhalensis and G. parilis are given as novel phylogenetic placements. In addition, we provide the morphology of Tarzetta tibetensis which was missing in the previous Fungal Diversity Notes 1611–1716. Identification of characterization of all these taxa are supported by morphological and multigene phylogenetic analyses.
Keywords: Ascomycota; Basidiomycota; Dothideomycetes; Fossil fungi; Glomeromycota; Lecanoromycetes; Leotiomycetes; Sordariomycetes